Hankel determinants for certain class of analytic functions subordinate with exponential functions / Nur Liana Mohd Rashidi, Ros Aida Daud and Shamilah Saad - Mohd Rashidi, Nur Liana; Daud, Ros Aida; Saad, Shamilah (2019)
In geometric functions theory, there are many subclasses that had been identified and introduced by researchers. It is normal for researchers to introduce new subclass of functions and find the related properties of that class of functions. We found out that there are not many existing projects that study on Hankel determinant for certain class of analytic functions subordinate with exponential functions. In this project, we aim to investigate the Hankel determinants which are Fekete-Szego functional, second Hankel determinant and third Hankel determinant for the class of functions subordinate with exponential functions.